The Effect of E-Service Quality and E-Trust on Generation Y E-Loyalty on Digital Banking Services in Indonesia - Lumbantobing, Angelia Tio; Komaladewi, Rita; Amar, Siti Chaerani Djen (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of Electronic Service Quality (E-Service Quality) and Electronic Trust (E-Trust) on Electronic Loyalty (E-Loyalty) among Generation Y users of digital banking services in Indonesia. A quantitative approach was employed involving 205 respondents, all of whom are Micro, Small, and Medium Enterprises (MSME) owners from Generation Y actively using digital banking services such as SeaBank, Bank Neo Commerce, and blu by BCA Digital. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3.0. The research instruments were proven to be valid and reliable, with outer loading values > 0.7, AVE > 0.5, and composite reliability > 0.7. The analysis results indicate that both E-Service Quality and E-Trust have a positive and significant effect on E-Loyalty. Furthermore, E-Trust also strengthens the relationship between service quality and user loyalty. The R-square value of 0.638 suggests that the model has a moderate ability to explain the endogenous variable. These findings provide practical implications for digital banks in enhancing user loyalty through reliable and secure services, as well as building long-term trust.